Closed-shell d10–d10 in [AuCl(CNR)]n and [AuCl(CO)]n (n = 1, 2; R = –H, –CH3, –Cy) complexes: quantum chemistry study of their electronic and optical properties. Issue 12 (7th March 2022) - Mendizabal, Fernando; Miranda-Rojas, Sebastián
Abstract : The [AuCl(CNR)] and [AuCl(CO)] (R = –H, –CH3, –Cy) complexes were modeled and their electronic and optical properties described. Abstract : The electronic structure and spectroscopic properties of [AuCl(CNR)] and [AuCl(CO)] (R = –H, –CH3, –Cy) complexes with d 10 –d 10 type interactions were studied at the post-Hartree–Fock (MP2, SCS-MP2, CCSD(T)) and density functional theory levels. It was found that the nature of the intermetal interactions is consistent with the presence of an electrostatic (dipole–dipole) contribution and a dispersion-type interaction. The absorption spectra of these complexes were calculated using the single excitation time-dependent (TD) method at the DFT and SCS-CC2 levels. The calculated values are in agreement with the experimental range, where the absorption and emission energies reproduce the experimental trends, with large Stokes shifts. According to this, intermetallic interactions were found to be mainly responsible for the metal–metal charge transfer (MMCT) electronic transitions among the models studied.